The use of eminent domain in São Paulo, Bogotá, and Mexico City. (2008)
In this work the author offers a rich and deep examination on the practices of “eminent domain” in three of the most important Latin-American cities. He approaches as the previous thing, of a critical way, the relations between the legal rules that concern of “eminent domain” and the institutional context in which the above mentioned rules are applied, in a two-dimensional perspective: the first one, that of the relations between the power judicial, legislative and executive in the relating thing to “eminent domain”, and the second one, the distribution of authority with relation to “eminent domain” to level of national, provincial or local governments. For this route the author achieves a guessed right comparative analysis, giving context to the above mentioned practices of “eminent domain”, in the reality of each one of this metropolis, allowing the inferences landed that similar studies lack.